Autonomic cardiac control response to walking and executive cognitive task in adolescents with acquired brain injury and typically developed controls. (12th May 2018) - Sorek, Gilad; Shaklai, Sharon; Meyer, Shirley; Katz-Leurer, Michal
ABSTRACT: Introduction : Adolescents with acquired brain injury (ABI) present a range of physical and cognitive as well as cardiac autonomic control system (CACS) dysfunctions. Aim : To examine the CACS response to an executive task, a physical task and a combined physical and executive task, in adolescents with ABI and typically developed (TD) controls. Methods : Included were two groups: The first group consisted of 17 adolescents (11–18 years) with ABI, during the in-patient or out-patient rehabilitation period. All were independent walkers. The second group consisted of 18-year-olds age and gender-matched TD adolescents. A Polar RS800CX device was used to assess heart rate (HR) and heart rate variability (HRV). Walking velocity was assessed by average speed on the 6-Minute Walk Test, and executive cognitive function was assessed by the Behavior Rating Inventory of Executive Function (BRIEF) questionnaire. The physical task was walking for 5 minutes on a treadmill. The cognitive task was the Digit Span Backward test. The study included four stages divided into rest state with and without cognitive task and walking state with and without cognitive task. Results : Adolescents with ABI presented higher HR and lower HRV measures at rest ( p -value < 0.01). A significant 'group' and 'activity' interaction effect on HRV was found; change in the activity level had significantly smaller effects on HRV parameters in adolescents with ABI as compared to controls. An interaction effect of 'cognitive' and 'activity' on HR and HRV was noted, with no significant difference between groups; at rest, performing a cognitive task was associated with reduced HRV, while during walking HRV increased. Conclusions : While ABI was associated with a reduced HRV at rest and less adaptive cardiac autonomic system to activity, ABI adolescent's response to a cognitive demand during an activity task such as walking was similar to the response of TD adolescents. Accordingly, we may say that adding a cognitive task to a walking task can improve the CACS function of ABI adolescents.